2008
DOI: 10.1007/s11255-008-9387-y
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of long-term graft function after kidney transplantation by intraoperative vascular complications

Abstract: Our data emphasize the importance of vascular complications compared to ureteral ones in kidney transplantation. Resolving 'non-urological' problems successfully, kidney transplantation is a safe procedure in urological hands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The mean time to these vascular complications was 1.8 months after transplantation. Fechner et al [20] reported significant impairment of kidney function and graft survival in patients who were re-operated for vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time to these vascular complications was 1.8 months after transplantation. Fechner et al [20] reported significant impairment of kidney function and graft survival in patients who were re-operated for vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, end to end anastomosis has been observed to have a worse rate of graft survival than end to side anastomosis and a threefold increased chance of developing stenosis (27). (28). In this research, we assessed the method for sequentially joining the internal iliac artery and the auxiliary lower polar graft artery end to side.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, end to end anastomosis had been observed to have a worse rate of graft survival than end to side anastomosis and to have a threefold greater chance of developing stenosis (35). (36).…”
Section: Discussionmentioning
confidence: 99%
“…This decision was based on kidney transplantation being major surgery involving the anastomosis of large vessels, with previous reports showing that 4.5–5.0% of kidney transplant recipients required surgical or radiologic reintervention for bleeding or graft hematoma . Hemorrhagic complications requiring surgical intervention significantly increase the risk of graft loss . We had avoided fibrinogen supplementation during peritoneal catheter placement out of consideration for its effect on future kidney transplantation, as acquired inhibitors can be produced after replacement therapy .…”
Section: Discussionmentioning
confidence: 99%